2021
DOI: 10.3390/economies9010014
|View full text |Cite
|
Sign up to set email alerts
|

Causal Interaction between FDI, Corruption and Environmental Quality in the MENA Region

Abstract: The present work analyzes the impact of foreign direct investment (FDI) and corruption on the quality of the environment in the MENA region. Indeed, the magnitude of corruption and the quality of institutions are often cited as the main factors affecting the FDI inflow. Here, the Autoregressive Distributed Lag (ARDL) approach was used to examine data on a group of MENA countries from 1990 to 2016. Our findings verify the Environmental Kuznets Curve. Furthermore, the empirical estimates approve the “pollution h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
(47 reference statements)
2
2
0
Order By: Relevance
“…Higher income of the countries contributes to high level of CO2 emission due to higher industries' activities. This is consistent with recent finding from [4] and [23]. The estimation results also indicate the EKC is valid with the respect to our sample.…”
Section: Resultssupporting
confidence: 93%
“…Higher income of the countries contributes to high level of CO2 emission due to higher industries' activities. This is consistent with recent finding from [4] and [23]. The estimation results also indicate the EKC is valid with the respect to our sample.…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, their results showed that biomass energy mitigated emissions, offering a complex picture of the variables affecting environmental results in the area. Bardi and Hfaiedh (2021) confirmed the existence of the EKC theory. Additionally, their research demonstrated a causal link, indicating that FDI influenced higher emissions and bolstered the Pollution Haven Hypothesis (PHH).…”
Section: Literature Reviewsupporting
confidence: 61%
“…The authors propose a network of conceptually related constructs that intervene in the process of bribery, i.e., relations under the influence of institutional dysfunction and connection and substantiality through action and culture. Bardi & Hfaiedh (2021) analyzed the impact of FDI and corruption on environmental quality in MENA countries in the period from 1990 to 2016. Their empirical assessments have confirmed the "pollution haven" hypothesis that the industrial activities of developed countries that pollute the environment are shifting to developing countries that have poorer environmental regulations.…”
Section: Overview Of Previous Researchmentioning
confidence: 99%